Impact of Punica granatum seeds extract (PSE) on renal and testicular tissues toxicity in mice exposed to iron oxide nanoparticles (IONPs) - Yasmin M. Abd El-Aziz; Fatima S. Alaryani; Nesreen Aljahdali; Kamlah Ali Majrashi; Najah M. Albaqami; Marwa S. Khattab; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Ali H. Abu Almaaty (Scientific Reports)
Abstract Recently, nano-manufactured materials have been used to treat many diseases, such as healing wounds and other modern biological applications. This study investigates the positive effect of Punica granatum seeds extract on kidney and testicular toxicities induced by iron oxide nanoparticles. Forty mice were randomly divided into four groups; the 1st group was the control group. The 2nd group was dosed daily with PSE at 100 g per kg. The 3rd group was dosed with 10 doses of iron oxide nanoparticles at 30 mg/kg b.wt of a mouse per day, 10 times only, then this toxic substance was withdrawn for the rest of the experimental period (30 days). The 4th group was dosed with the same doses as the second and third groups. In this research, we focused on the possibility of using the positive curative effects of PSE, which were estimated at the level of blood chemistry biomarkers, as well as histological and histochemical examinations for the kidney and testis after exposure of mice to iron oxide nanoparticles. These aim to clarify the effect of iron oxide nanoparticles on kidney and testicular morphology and their functions, as well as the potential ameliorative effects of PSE.